Dietary phytochemicals in the protection against oxysterol-induced damage. (October 2017) - Cilla, Antonio; Alegría, Amparo; Attanzio, Alessandro; Garcia-Llatas, Guadalupe; Tesoriere, Luisa; Livrea, Maria A.
Highlights: Sterol oxidation products (SOPs) implied in the origin of different pathophysiological conditions. Description of distinct studies in various cell models evidencing protection against SOPs toxicity by dietary phytochemicals. Prevention of SOPs injury through modulation of intracellular signaling cascades beyond direct antioxidant activity. Perspectives and recommendations on further research needed in the field of oxysterol injury prevention. Abstract: The intake of fruits and vegetables is associated with reduced incidence of many chronic diseases. These foods contain phytochemicals that often possess antioxidant and free radical scavenging capacity and show anti-inflammatory action, which are also the basis of other bioactivities and health benefits, such as anticancer, anti-aging, and protective action for cardiovascular diseases, diabetes mellitus, obesity and neurodegenerative disorders. Many factors can be included in the etiopathogenesis of all of these multifactorial diseases that involve oxidative stress, inflammation and/or cell death processes, oxysterols, i.e. cholesterol oxidation products (COPs) as well as phytosterol oxidation products (POPs), among others. These oxidized lipids result from either spontaneous and/or enzymatic oxidation of cholesterol/phytosterols on the steroid nucleus or on the side chain and their critical roles in the pathophysiology of the abovementioned diseases has become increasingly evident. In this context, many studies investigated the potential of dietary phytochemicals (polyphenols, carotenoids and vitamins C and E, among others) to protect against oxysterol toxicity in various cell models mimicking pathophysiological conditions. This review, summarizing the mechanisms involved in the chemopreventive effect of phytochemicals against the injury by oxysterols may constitute a step forward to consider the importance of preventive strategies on a nutritional point of view to decrease the burden of many age-related chronic diseases.